Organic Reactions 1977
DOI: 10.1002/0471264180.or025.01
|View full text |Cite
|
Sign up to set email alerts
|

The R amberg‐ B äcklund Rearrangement

Abstract: The halogen atoms of α‐halo sulfones, in contrast to halogen atoms α to other electron‐withdrawing functionalities, show marked resistance to substitution by external nucleophiles. Seemingly, polar, steric, and field effects combine to repel nucleophilic species. However, the same α‐sulfonyl halogen atoms are capable of facile intramolecular 1,3 elimination, leading to replacement of the sulfonyl group by a carboncarbon double bond with loss of halide and sulfite ions. This extrusion process, frequently refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 89 publications
0
34
0
Order By: Relevance
“…[126] The xanthate group in the adducts constitutes a convenient entry into all of organosulfur chemistry. The RambergÀ Bäcklund olefin forming reaction, [92][93] the numerous reactions involving sulfur ylides, and the rich chemistry of sulfones can all participate in mutually enriching symbiotic alliances with the radical chemistry of xanthates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[126] The xanthate group in the adducts constitutes a convenient entry into all of organosulfur chemistry. The RambergÀ Bäcklund olefin forming reaction, [92][93] the numerous reactions involving sulfur ylides, and the rich chemistry of sulfones can all participate in mutually enriching symbiotic alliances with the radical chemistry of xanthates.…”
Section: Discussionmentioning
confidence: 99%
“…[91] In our case, not only did the HWE condensation on diketone 212 take place smoothly, but the product 213 contains a xanthate group on C(11) that could later be used to introduce the exo-methylene group found in Desogestrel, for example by a RambergÀ Bäcklund reaction. [92,93] An alternative way to exploit the HWE condensation is to have the phosphonate on the alkene and the xanthate attached to the ketone. This variant is illustrated by the transformations in Scheme 33.…”
Section: An Alliance With the Horner -Wadsworth-emmons Condensationmentioning
confidence: 99%
“…Sulfoxides are well-known for enabling syn eliminations, Mislow–Evans rearrangements, , Pummerer reactions, , and sulfoxide–metal exchanges , while also acting as a useful ligand class for transition metal catalysis . The higher-oxidation state sulfones also provide ample opportunities in organic synthesis, most notably as alkene precursors in the Julia–Lythgoe olefination, , Kocienski-modified Julia olefination, , and Ramberg–Bäcklund rearrangement. , A recent report has also highlighted the utility of sulfones as radical cross-coupling partners . The preparation of alkyl thioethers generally proceeds through nucleophilic displacement of a (pseudo)­halide with a thiol or the trapping of an alkyl radical or organometallic nucleophile with a disulfide .…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of alcohol 5 into methylenic derivative 3 is believed to result from the Ramberg-Bäcklund reaction 8 and occurs in a tandem process of 1,3-dehydrobromination to give episulfone 9 followed by its desulfonation. Although attempts at detecting episulfone 9 during the treatment of alcohol 5 with a base failed, it may be assumed that the stereochemistry of alcohol 5 1,3-dehydrobromination is the same as that of ether 6.…”
mentioning
confidence: 99%
“…Although attempts at detecting episulfone 9 during the treatment of alcohol 5 with a base failed, it may be assumed that the stereochemistry of alcohol 5 1,3-dehydrobromination is the same as that of ether 6. Furthermore, literature precedents 8,9 suggest that α-bromosulfones 5 and 6 should indeed undergo stereoselective dehydrobromination to give episulfones 9 and 8, respectively, since it has been found that elimination obeys the W-stereochemistry 10 and the α-proton is abstracted from a conformation of the starting bromosulfone in which it is flanked by oxygen atoms of the sulfo group. Thus, alcohol 3 is formed due to fragmentation of episulfone 9 and is a 'normal' product of the Ramberg-Bäcklund reaction (Scheme 3).…”
mentioning
confidence: 99%